Czartoryski & Torlonia: A Collection of Roman Marble Statues in the Princes Czartoryski Museum - Dorota Gorzelany-Nowak (Studies in Ancient Art and Civilization, 2019)
The objective of the article is to discuss the history of the acquiring of marble sculptures by Prince Władysław Czartoryski during his two stays in Italy: in Naples in 1889 and in Rome in 1891, based on preserved archival documents. The statues include such exquisite examples as a sculpture of Venus Medici from the beginning of the 1st century AD, as well as examples of compilations of ancient fragments that supposedly had previously belonged to the Roman Torlonia collection. Formal analysis of individual objects is expanded upon with information related to conservations they have been subject to.